Innovation of the Internship Program and Its Implications for the Soft Skill Development of Prospective Islamic Religious Education Teachers at Sunan Kalijaga State Islamic University, Yogyakarta - Sukiman; RR. Umi Baroroh; Aninditya Sri Nugraheni; Abdulrahman Sama-alee (Jurnal Pendidikan Agama Islam, 2024)
Purpose – The objectives of this study are (1) to analyze the innovation in the implementation of internship activities at FITK and (2) to analyze the impact of internships on the soft skill development of prospective PAI teachers. Design/methods/approach – This study is qualitative research. The background of the research is the PAI Study Program, Faculty of Tarbiyah Sciences, UIN Sunan Kalijaga Yogyakarta. The informants of this research are four (4) laboratory managers, four (4) field supervisors, and 14 students of the PAI Study Program at UIN Sunan Kalijaga Yogyakarta. Data collection techniques used in-depth interviews, FGDs, and documentation. Data analysis techniques included the stages of data condensation, data display, and concluding/verification. The validity test of the data used a triangulation technique, which included two ways, namely source triangulation and technique. Findings – First, the innovation of the Integrative Internship program at the Faculty of Tarbiyah and Teacher Training has been applied in the form of giving students more freedom to choose a place and formulating the type and form of internship according to the conditions and needs in the field where they are interning. Second, implementing the Integrative Internship program has had advantages in developing students' soft skills. The developed soft skills have included six types, namely communication and relationship-building skills, critical thinking and problem-solving skills, teamwork skills, leadership skills, stress management, and creativity. Research implications/limitations – Implementing the integrative independent internship program has provided broad authority to students. This authority has implications for developing students' soft skills. Therefore, the granting of this authority can be continued in the future. Improvements must be made by optimizing the role of DPL, pamong teachers, and schools/madrasas in providing services and guidance more optimally so that the development of students' hard skills and soft skills can be maximized.